Adoption behavior of halal food logistics in food and beverages industry - Norlila, Mahidin (2018)
Halal Food Logistics (HFL) service providers are one of the most important components in the Supply Chain Management that involves the activities of planning, organizing, implementing and controlling the performance of a business operation in an effective and efficient manner. Due to this , most of the industry players tend to apply the approach of outsourcing the firm services including the storage of goods/products, service operation, transportation and related information from the point of consumption in order to stay competitive with other companies in the Food and Beverages (F&B) industry. The expansion of business and increment in this intense competition has aroused many F & B manufactures to develop logistics as a part of their corporate strategy for cost and service advantages. Therefore, many logistics service providers are moving towards catering to the demands of the halal industry based on the halal trend that is being reviewed mostly as one of the profitable platforms for the business lately. This study examined the adoption behavior of HFL in the small medium enterprises (SMEs) of F & B manufacturers. A theoretical framework was constructed based on the perspective of the Theory of Planned Behavior to describe the relationships among the variables. Data was collected through a survey of 300 F & B manufacturers among the SME industries in Malaysia. Out of the 153 questionnaires returned which brought the response rate of about 51 %, only 141 were usable. The empirical results showed that the subjective norms, knowledge and perceived risk have significant relationships with the actual adoption of HFL services among the F & B manufacturers in Malaysia. The results also demonstrated that intention and trust have mediating effects on the strength of the relationships between the subjective norms, knowledge and perceived risk and the actual adoption behavior of the HFL services in Malaysia.